Taurine cross-linked salicylic acid nano-composite gel for efficient transdermal delivery and mild acne removal as well as preparation method and application of taurine cross-linked salicylic acid nano-composite gel

Through taurine-crosslinked salicylic acid nanocomposite gel, the synergistic effect of salicylic acid and quaternary ammonium salt-73 was used to solve the problems of large irritation and poor absorption of ingredients in existing acne-removing products, achieving high efficiency, Gentle acne treatment and skin barrier repair significantly reduce acne symptoms.

CN119157780APending Publication Date: 2024-12-20BEIJING PROTA BIOTECHNOLOGY GROUP CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411308109.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing acne-removing products have high irritation of hormones, antibiotics and other ingredients, resulting in increased skin resistance, poor acne removal effect, lack of skin barrier repair, and the effective ingredients are difficult to penetrate the skin and absorb, resulting in repeated acne.

Method used

Salicylic acid nanocomposite gel crosslinked using taurine, containing salicylic acid, quaternary ammonium salt-73, taurine, polyol, lipids, emulsifiers, co-emulsifiers, antioxidants and water, through nano Chemical treatment forms nanocomposite gels with particle size of 10-100nm, and use taurine preferential absorption to promote the transdermal absorption of salicylic acid and quaternary ammonium salt-73, and synergistically achieves gentle and efficient acne removal and skin barrier repair.

Benefits of technology

It achieves efficient transdermal delivery, quickly removes acne, reduces irritation, improves skin immunity, regulates water and oil balance, improves skin texture and barrier function, significantly reduces acne symptoms and avoids acne marks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049859330000081
    Figure BDA0005049859330000081
  • Figure BDA0005049859330000091
    Figure BDA0005049859330000091
  • Figure BDA0005049859330000111
    Figure BDA0005049859330000111
Patent Text Reader

Abstract

The invention relates to taurine cross-linked salicylic acid nano-composite gel for efficient transdermal delivery and mild acne removal as well as a preparation method and application of the taurine cross-linked salicylic acid nano-composite gel. The nano-gel comprises salicylic acid, quaternary ammonium salt-73, taurine, polyol, lipid, an emulsifier, a co-emulsifier, an antioxidant and water. Salicylic acid, quaternary ammonium salt-73 and taurine are used as functional components for removing acnes. Salicylic acid can decompose grease on the surface of the skin, so that the oil control effect is achieved, meanwhile, skin metabolism is promoted, angular suppository is loosened, pores are dredged, and acne is treated; quaternary ammonium salt-73 has extremely high antibacterial activity, especially has a remarkable antibacterial effect on propionibacterium acnes causing acnes, and can quickly and thoroughly remove the acnes by being matched with salicylic acid; taurine provides energy required by normal physiological activities of human cells, improves skin immunity, regulates skin water-oil balance and has the effects of improving skin textures, dryness, wrinkles, elasticity, sensitivity and other skin problems, meanwhile, in the using process, taurine is preferentially absorbed by the skin, so that an inclusion shell is broken, and the skin is protected. Rapid release and transdermal absorption of salicylic acid and quaternary ammonium salt-73 are promoted, irritation is reduced, and the three components act synergistically to achieve the functions of mildly, efficiently and rapidly treating acne and reconstructing skin barrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of cosmetics, and in particular relates to a taurine-crosslinked salicylic acid nanocomposite gel for efficient transdermal delivery and mild acne removal, as well as a preparation method and application thereof. Background Art

[0002] Acne is the most common chronic inflammatory disease of the hair follicles and sebaceous glands in dermatology. Its pathogenesis is complex and caused by multiple factors, including abnormal keratinization of the hair follicles and sebaceous gland ducts, excessive secretion of sebaceous glands, inflammatory response, and the proliferation of Propionibacterium acnes. Clinically, the severity of acne is summarized as "three degrees and four levels", namely mild (level 1): only comedones; moderate (level 2): ​​inflammatory papules; moderate (level 3): pus cells; severe (level 4): nodules and cysts. Acne can reduce patients' self-confidence, reduce their quality of life, cause depression, and even cause mental disorders.

[0003] At present, the products on the market have the following problems: 1) Many existing acne removal products on the market use hormones, antibiotics, retinoic acid, sulfur, fruit acid and other ingredients, which are highly irritating to the skin and easily cause the skin to resist Propionibacterium acnes. Their safety is constantly questioned, and they lack skin barrier repair while removing acne. 2) Most acne-removing cosmetics are directly applied to the acne area, and the effective acne-removing ingredients cannot penetrate the epidermis well for absorption, and the ingredients in the formula design have a single efficacy, resulting in poor acne removal effect or repeated acne, causing patients to lose confidence.

[0004] Therefore, there is an urgent need for an acne removal product in this field that can remove acne gently, quickly and efficiently. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides a taurine-crosslinked salicylic acid nanocomposite gel with high efficiency, transdermal delivery and mild acne removal, as well as a preparation method and application thereof. The salicylic acid nanocomposite gel comprises salicylic acid, quaternary ammonium salt-73, taurine, polyols, lipids, emulsifiers, co-emulsifiers, antioxidants and water. By selecting salicylic acid, quaternary ammonium salt-73 and taurine as effective ingredients for removing acne, salicylic acid can decompose the oil on the skin surface, thereby achieving the effect of oil control, while promoting skin metabolism, loosening keratin plugs, unclogging pores and treating acne; quaternary ammonium salt-73 has It has strong antibacterial activity, especially for Propionibacterium acnes that causes acne. It can quickly and thoroughly remove acne when combined with salicylic acid. Taurine provides the energy required for normal physiological activities of human cells, enhances skin immunity, regulates the water and oil balance of the skin, and also has the effect of improving skin texture, dryness, wrinkles, elasticity, sensitivity and other skin problems. At the same time, during use, taurine is preferentially absorbed by the skin, causing the outer shell of the inclusion to rupture, promoting the rapid release and transdermal absorption of salicylic acid and quaternary ammonium salt-73, and reducing irritation. The synergistic effect of the three can achieve the function of gently, efficiently and quickly treating acne and rebuilding the skin barrier.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical scheme: a taurine-crosslinked salicylic acid nanocomposite gel with high efficiency, transdermal delivery and mild acne removal, wherein the salicylic acid nanocomposite gel comprises salicylic acid, quaternary ammonium salt-73, taurine, polyol, lipid, emulsifier, co-emulsifier, antioxidant and water.

[0007] In a preferred embodiment of the present invention, the mass percentages of quaternary ammonium salt-73, salicylic acid, and taurine are (0.0001-1wt%): (20-40%): (0.001-3%).

[0008] In a preferred embodiment of the present invention, the formula components and mass percentages of the salicylic acid nanocomposite gel are as follows:

[0009] Polyol 15-30wt%;

[0010] Lipid 5~20wt%

[0011] Emulsifier 5~30wt%

[0012] Emulsifier 15~40wt%

[0013] Antioxidant 0.1~3wt%

[0014] Quaternary ammonium salt-73 0.0001~1wt%

[0015] Salicylic acid 20~35wt%

[0016] Taurine 0.001~3%

[0017] The rest was deionized water.

[0018] In a preferred embodiment of the present invention, the mass percentage of salicylic acid is 20-35%, more preferably 30%. The salicylic acid can decompose the oil on the skin surface, thereby achieving the effect of oil control, while promoting skin metabolism, loosening keratin plugs, unclogging pores, and treating acne.

[0019] In a preferred embodiment of the present invention, the mass percentage of the quaternary ammonium salt-73 is 0.0001-0.5wt%, more preferably 0.5%. The quaternary ammonium salt-73 has extremely strong antibacterial activity, can effectively inhibit the excessive reproduction of pathogens such as Propionibacterium acnes, and can quickly and thoroughly remove acne when combined with salicylic acid.

[0020] In a preferred embodiment of the present invention, the mass percentage of taurine is 0.01-3%, more preferably 3%. The taurine provides energy required for normal physiological activities of human cells, enhances skin immunity, regulates the water-oil balance of the skin, and also has the effect of improving skin texture, dryness, wrinkles, elasticity, sensitivity and other skin problems. At the same time, during use, taurine is preferentially absorbed by the skin, resulting in rupture of the outer shell of the inclusion body, promoting the rapid release and transdermal absorption of salicylic acid and quaternary ammonium salt-73, and reducing irritation; the synergistic effect of the three achieves the function of mild, efficient and rapid treatment of acne and reconstruction of the skin barrier.

[0021] In a preferred embodiment of the present invention, the mass percentage of the polyol is 15% to 30wt%. The polyol is selected from one or more of glycerol, sorbitol, polyethylene glycol-400, 1,2-butylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, 1,2-hexanediol, 1,2-pentanediol, and octyl dodecanol.

[0022] In a preferred embodiment of the present invention, the mass percentage of the lipid is 5% to 20wt%; the lipid is selected from one or more of vegetable oil, isopropyl palmitate, isopropyl myristate, caprylic / capric triglyceride, polyethylene glycol lauric acid glyceride, caprylic / capric acid polyethylene glycol glyceride, polyethylene glycol stearic acid glyceride, glyceryl stearate, linoleic acid glyceride, caprylic / capric acid cocoa butter, propylene glycol monocaprylate, dicaprylic / capric propylene glycol ester, acetylated monoglyceride, cetyl alcohol, stearyl alcohol and cetearyl alcohol.

[0023] In a preferred embodiment of the present invention, the mass percentage of the emulsifier is 5% to 30wt%. The emulsifier is selected from one or more of PEG-15 lauryl glyceride, polysorbate-20, polysorbate-60, polysorbate-80, PEG-12 stearate, PEG-24 cholesteryl ether, PEG-40 hydrogenated castor oil, sucrose stearate, and PEG-20 methyl glucose sesquistearate.

[0024] In a preferred embodiment of the present invention, the mass percentage of the co-emulsifier is 15% to 40wt%; the co-emulsifier is selected from one or more of PPG-26-butanol polyether-26, diethoxydiglycol, tridecyl alcohol polyether-9, coconut oil alcohol polyether-7, and PPG-1-PEG-9 lauryl glycol ether.

[0025] In a preferred embodiment of the present invention, the antioxidant is selected from one or more of tocopherol acetate, sodium gluconate, tocopherol (vitamin E), and tert-butylparamethoxyphenol.

[0026] The present invention also protects a method for preparing the salicylic acid nanocomposite gel, comprising the following steps:

[0027] 1) mixing lipid, salicylic acid, quaternary ammonium salt-73, antioxidant, emulsifier and co-emulsifier to obtain an oil phase;

[0028] 2) mixing polyol, taurine and deionized water to obtain an aqueous phase;

[0029] 3) adding the water phase to the oil phase, and after mixing, performing micronization treatment after mixing to obtain a micron-sized dispersion;

[0030] 4) subjecting the micron-scale dispersion to nano-treatment to obtain the salicylic acid nanocomposite gel.

[0031] In a preferred embodiment of the present invention, in step 1), the mixing temperature is preferably 25 to 75° C., more preferably 50 to 65° C. The mixing of the present invention is preferably carried out in a water bath until the components are evenly dispersed.

[0032] In a preferred embodiment of the present invention, in step 2), the mixing temperature is preferably 25 to 75° C., more preferably 50 to 65° C. The mixing of the present invention is preferably carried out in a water bath until the components are evenly dispersed.

[0033] In a preferred embodiment of the present invention, in step 3), the aqueous phase is added to the oil phase under stirring; the stirring speed is preferably 200-600 rpm; the method for achieving the micronization treatment includes high-speed shear emulsification; the speed of the high-speed shear emulsification is 2000-10000 rpm, preferably 5000-10000 rpm, and the time is 3-15 min, preferably 3-6 min.

[0034] In a preferred embodiment of the present invention, in step 4), the method of achieving the nano-treatment includes high-pressure homogenization treatment or high-speed microfluidization treatment; the pressure of the high-pressure homogenization treatment is 400-1500 bar, preferably 300-1600 bar; the number of treatments is 2-10 times, preferably 2-6 times; the pressure of the high-pressure microfluidization treatment is 200-2000 bar, preferably 300-2000 bar, and the number of treatments is 2-10 times, preferably 2-6 times.

[0035] In a preferred embodiment of the present invention, the prepared salicylic acid nanocomposite gel particles have a particle size of 10-100 nm and are nanocomposites.

[0036] The present invention also protects the application of the salicylic acid nanocomposite gel in the preparation of cosmetics.

[0037] In a preferred embodiment of the present invention, the application includes application in improving and treating acne, and the method of use is compounding or direct application.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. Transdermal absorption: Taurine can simultaneously enhance the transdermal absorption effect of salicylic acid and quaternary ammonium salt-73 (pione).

[0040] 2. Remove acne and repair the skin barrier at the same time: Taurine provides the energy required for normal physiological activities of human cells, enhances skin immunity, regulates the water and oil balance of the skin, and also has the effect of improving skin texture, dryness, wrinkles, elasticity, sensitivity and other skin problems, and reduces irritation caused during use.

[0041] 3. Synergistic effect, strong efficacy: Salicylic acid can remove blackheads and acne, mainly relying on its ability to penetrate deep into the pores through the sebaceous glands, dissolve oil, remove blackheads and acne, improve pore blockage, and regulate cuticles and regulate the water and oil balance of the skin, making it the best choice for removing acne. Quaternary ammonium salt-73 is a powerful antibacterial agent, which has antibacterial and bactericidal effects on follicular inflammation and Propionibacterium acnes and Staphylococcus aureus that cause skin suppuration or infection. Clinical studies have shown that its MIC for Propionibacterium acnes is 0.00002%, and the rash can be reduced by 50% after two weeks of use, which can effectively improve and treat acne.

[0042] 4. Since the pathogenesis of acne is relatively complex. Therefore, removing acne is a comprehensive process, which must meet the following aspects at the same time: 1) Regulate oil secretion, soften keratin, and open the blocked sebaceous gland duct. Salicylic acid has significant effects in this regard. 2) At the same time, it inhibits Propionibacterium acnes and Staphylococcus aureus. Clinical studies have shown that quaternary ammonium salt-73 has antibacterial and bactericidal effects on follicular inflammation and Propionibacterium acnes, Staphylococcus aureus, etc. that cause skin suppuration or infection. The MIC for Propionibacterium acnes is 0.00002%, and the rash can be reduced by 50% after two weeks of use. 3) Because various skin inflammations such as inflammatory papules, pustules, nodules and cysts will eventually destroy the skin barrier, and even produce acne scars, etc. Taurine repairs damaged skin and enhances skin immunity, thereby avoiding products with various skin problems. The three active ingredients with different mechanisms are matched with each other and synergistically enhanced, so as to achieve efficient and gentle maximization of acne removal, repair of damaged skin, and reconstruction of skin barrier function. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The following is a further description with reference to the accompanying drawings.

[0044] Figure 1 The figure is a statistical graph of the cumulative penetration percentage test obtained in the embodiments and comparative examples.

[0045] Figure 2 Surface appearance of salicylic acid nanocomposite gel in the embodiment and comparative example in the human body acne removal test. DETAILED DESCRIPTION

[0046] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0047] Embodiment 1:

[0048] A taurine-crosslinked salicylic acid nanocomposite gel with high efficiency, transdermal delivery and mild acne removal, and a preparation method thereof is as follows:

[0049] (1) at 45° C., 30 wt % salicylic acid, 2 wt % caprylic / capric triglyceride, 0.5 wt % quaternary ammonium salt-73, 1 wt % tocopherol (vitamin E), 5 wt % polysorbate-20, and 2 wt % diethoxydiglycol are stirred at 30° C. and 600 rpm to obtain an oil phase for standby use;

[0050] (2) 20 wt% of 1,2-pentanediol, 5 wt% of 1,3-propylene glycol, 3 wt% of taurine and the remainder of water were mixed and stirred at 45° C. to obtain an aqueous phase;

[0051] (3) slowly adding the aqueous phase to the prepared oil phase at 45° C. and stirring continuously at a rotation rate of 600 r / min. After the mixing is completed, high-speed shear emulsification is performed at a rotation speed of 7000 rpm for 6 min to obtain a micron-sized dispersion;

[0052] (4) The prepared micron-sized dispersion was subjected to high-pressure microfluidization treatment for three times at 1500 bar and then cooled to room temperature to obtain the salicylic acid nanocomposite gel capable of transdermal delivery and mild acne removal as described in Example 1.

[0053] Embodiment 2:

[0054] A taurine-crosslinked salicylic acid nanocomposite gel with high efficiency, transdermal delivery and mild acne removal, and a preparation method thereof is as follows:

[0055] (1) at 45° C., 30 wt % salicylic acid, 2 wt % caprylic / capric triglyceride, 0.1 wt % quaternary ammonium salt-73, 1 wt % tocopherol (vitamin E), 5 wt % polysorbate-20, and 2 % diethoxydiglycol are stirred at 30° C. and 600 rpm to obtain an oil phase for standby use;

[0056] (2) 20 wt% glycerol, 5 wt% 1,3-propylene glycol, 0.5 wt% taurine and the remainder of water were mixed and stirred at 45° C. to obtain an aqueous phase;

[0057] (3) slowly adding the aqueous phase to the prepared oil phase at 45° C. and stirring continuously at a rotation rate of 600 r / min. After the mixing is completed, high-speed shear emulsification is performed at a rotation speed of 7000 rpm for 6 min to obtain a micron-sized dispersion;

[0058] (4) The prepared micron-sized dispersion was subjected to high-pressure microfluidization treatment for three times at 1500 bar and then cooled to room temperature to obtain the salicylic acid nanocomposite gel of Example 2.

[0059] Embodiment 3:

[0060] A taurine-crosslinked salicylic acid nanocomposite gel with high efficiency, transdermal delivery and mild acne removal, and a preparation method thereof is as follows:

[0061] (1) at 45° C., 30 wt % salicylic acid, 2 wt % propylene glycol monocaprylate, 0.1 wt % quaternary ammonium salt-73, 1 wt % tocopherol (vitamin E), 5 wt % PEG-40 hydrogenated castor oil, and 5 wt % cocoether-7 are stirred at 30° C. and 600 rpm to obtain an oil phase for standby use;

[0062] (2) 20 wt% glycerol, 5 wt% 1,3-propylene glycol, 3 wt% taurine and the remainder of water were mixed and stirred at 45° C. to obtain an aqueous phase;

[0063] (3) slowly adding the aqueous phase to the prepared oil phase at 45° C. and stirring continuously at a rotation rate of 600 r / min. After the mixing is completed, high-speed shear emulsification is performed at a rotation speed of 7000 rpm for 6 min to obtain a micron-sized dispersion;

[0064] (4) The prepared micron-sized dispersion was subjected to high-pressure microfluidization treatment for three times at 1500 bar and then cooled to room temperature to obtain the salicylic acid nanocomposite gel of Example 3.

[0065] Comparative Examples 1-4

[0066] Comparative Example 1-4 is the same as Example 1-3, except that when preparing the composite gel, the proportions of salicylic acid, quaternary ammonium salt-73, and taurine are different. The specific differences are listed in Table 1.

[0067] Comparative Examples 5-6

[0068] Referring to Example 1-2 of the present invention, salicylic acid and quaternary ammonium salt are not packaged but only dissolved in a solvent to form a solution with a salicylic acid content of 30%, a quaternary ammonium salt content of 0.5% and 0.1%, and a taurine content of 3% and 0.5%.

[0069] Table 1 Concentration of active ingredients (mass percentage %)

[0070]

[0071]

[0072] Test Example 1

[0073] The nano gels obtained in the above examples and comparative examples and the aqueous solutions diluted 2 times by the laser particle size analyzer were tested for particle size. Except for comparative examples 5-6, the particle sizes were all around 25 nm. The nano composite gels were placed in a sealed container at room temperature, 4°C, -18°C and 45°C for 60 days. A large amount of crystals were precipitated in comparative examples 5-6, and the system was unstable. Except for comparative examples 5-6, the remaining nano composite gels had no agglomeration, discoloration, stratification, crystal precipitation, and no significant change in particle size. The stability was good, indicating that the nano preparation method of the present invention can effectively stabilize the system and avoid the precipitation of active crystals.

[0074] Test Example 2

[0075] In vitro skin permeation test

[0076] After the experimental animals are anesthetized, the skin is prepared and removed. Use pure water or saline to rinse the outer surface of the skin, and use surgical scissors to carefully scrape off the remaining subcutaneous fat, capillaries and other tissues, then rinse it repeatedly with pure water or saline for later use. Select a PBS solution containing 20% ​​propylene glycol as the receiving solution. Fix the ex vivo skin in a Franz diffusion cell with the stratum corneum facing up, add the receiving solution to the receiving chamber, and put the diffusion cell with the skin and the receiving solution into a transdermal diffusion instrument at 100-600r / min. After balancing for 30 minutes, use an ear bulb to remove the bubbles in the diffusion cell. Accurately measure the supply solution or the test preparation in the supply chamber, use a syringe to absorb the receiving solution at different time points, and promptly replenish the same volume of isothermal fresh receiving solution. Take a sample of the receiving solution every 24 hours, centrifuge it at 12000r / min for 10 minutes, take the supernatant and use HPLC to determine the content of salicylic acid and quaternary ammonium salt-73 in the receiving solution, among which,

[0077] Cumulative penetration percentage Q% = cumulative permeation amount / total amount of drug administration

[0078] The cumulative transmittance test results of Examples 1-3 and Comparative Examples 1-2 and 5-6 are as follows: Figure 1 As shown, salicylic acid and quaternary ammonium salt-73 in Example 1 have higher cumulative skin penetration percentages, which are as high as 6.54% and 5.22%, respectively, indicating that the presence of taurine significantly increases the skin permeability of salicylic acid and quaternary ammonium salt-73 in the nanocomposite gel.

[0079] Test Example 3

[0080] Antibacterial experiment

[0081] The nanogels obtained in Examples 1-3 and Comparative Examples 1-6 were diluted 2 times as samples to be tested; a small amount of Propionibacterium acnes and Malassezia on the surface of the activated culture medium were picked up with an inoculation loop, sterile saline was added, and the mixture was evenly dispersed in the sterile saline by oscillation on an oscillator. The corresponding proportions were diluted or concentrated until the absorbance of the bacterial solution at 600nm was about 1±0.2. The bacterial solution whose absorbance met the experimental requirements was diluted 320 times, mixed and added, and the well plate was gently shaken after inoculation to mix the solution (blank group: 200uL, malt broth culture medium; negative group: 100uL malt broth culture medium + 100uL bacterial solution; positive group 100uL malt broth culture medium + 100uL 64ug / mL ketoconazole solution; sample group: 100uL malt broth culture medium + 100uL sample diluent). A circle of PBS was added to the outside as the zeroing hole. After all the samples were added, the well was sealed with a sealing film and incubated at 37°C in a biochemical incubator for 24 hours. The absorbance of the well plate at 600 nm was detected using an ELISA reader. The results are shown in Table 2.

[0082] Sample inhibition rate (%) = (negative - sample) / (negative - blank) * 100%

[0083] Table 2 Nanogel antibacterial test results

[0084]

[0085] If the inhibition rate is between 50% and 90%, it is considered to have an antibacterial effect; if the inhibition rate is ≥90%, it is considered to have a strong antibacterial effect. If the inhibition rate is ≤50%, it is considered to have no antibacterial effect.

[0086] According to Table 2, compared with Comparative Example 1, the sample of Example 1 has better antibacterial effect on Propionibacterium acnes and Malassezia, and the antibacterial rates are 77.74%±4.8% and 99.58%±0.28%, respectively. This may be because the presence of taurine in Example 1 increases the permeability of the bacterial cell wall, allowing salicylic acid and quaternary ammonium salt-73 to better exert their antibacterial effects.

[0087] Test Example 4

[0088] Skin irritation test

[0089] 45 healthy rabbits weighing (2.0±0.2) kg were randomly divided into 9 groups, with 5 animals in each group. The hair on both sides of the rabbit back skin was removed 24 hours before the experiment. The hair-removed skin was checked for damage 24 hours after the hair removal. The damaged skin was not suitable for skin irritation test. The nanogel obtained by using Examples 1-3 was applied 3 times a day for 7 consecutive days, and the comparative examples 1-6 were applied at the same time for control. The test results were observed and the test results are listed in Table 3.

[0090] Table 3 Observation results of nanogel skin irritation

[0091]

[0092] “+” means the rabbit’s skin is congested, red and swollen; “++” means the congestion, redness and swelling are still there, but there is an increasing trend; “—” means there is no congestion, redness and swelling.

[0093] According to the test results in Table 3, it can be seen that the nanogels prepared by using the anti-acne composites prepared by Examples 1-3 and Comparative Examples 1-4 were applied to the rabbit skin without congestion and redness, indicating that the salicylic acid mass percentage content in the nanogel provided by the present invention is 30% and the quaternary ammonium salt mass percentage content is within 0.5%, and there is no irritation to the skin. Comparative Examples 5 and 6 showed congestion and redness on the 6th day, indicating that unencapsulated salicylic acid and quaternary ammonium salt-73 will cause irritation.

[0094] Test Example 5

[0095] 70 volunteers aged 18 to 45 years old, half male and half female, with similar acne size and area were selected. After facial cleaning, facial images were taken using a VISIA facial image analyzer to analyze facial skin lesions. The nanogels prepared in Examples 1-3 and Comparative Examples 1-4 were used to take photos with a VISIA instrument to measure the initial red pigment index and acne status of the facial skin of the above 70 volunteers, and the improvement degree of facial acne of the volunteers after trying the relevant products for 5 days was measured and recorded. The specific test results are shown in Table 4.

[0096] Table 4 Comparison of improvement of facial acne in volunteers

[0097]

[0098] According to the data in the table and the actual observation of volunteers, the acne index of the facial skin of the volunteers who tried the nanogels of Examples 1-3 was significantly reduced, proving that the effective components of the nanogels of Examples 1-3 are well-proportioned and can effectively eliminate, improve and treat acne symptoms. At the same time, compared with Example 1, the acne removal effect of Example 2 is significantly reduced, which may be due to the decrease in the mass percentage of taurine, which weakens the release and transdermal effect of salicylic acid and quaternary ammonium salt-73 in the nanogel, thereby weakening the overall acne removal effect. The specific appearance diagram is as follows: Figure 2 shown.

[0099] It can be seen from the above examples that the nanogel provided by the present invention has good stability, large drug loading capacity, no irritation and significant anti-acne effect, and the preparation method of the present invention is simple, easy to control, and suitable for industrial and large-scale production.

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A taurine cross-linked salicylic acid nanocomposite gel with high efficiency, transdermal delivery and mild acne removal, characterized in that: The salicylic acid nanocomposite gel comprises salicylic acid, quaternary ammonium salt-73, taurine, polyol, lipid, emulsifier, co-emulsifier, antioxidant and water.

2. The salicylic acid nanocomposite gel according to claim 1, characterized in that: The mass percentages of quaternary ammonium salt-73, salicylic acid and taurine are (0.0001-1wt%): (20-40%): (0.001-3%).

3. The salicylic acid nanocomposite gel according to claim 1, characterized in that: The formula ingredients and mass percentages of the salicylic acid nanocomposite gel are as follows: Polyol 10-30wt%; Lipid 1~20wt% Emulsifier 1~30wt% Emulsifier 10~40wt% Antioxidant 0.1~5wt% Quaternary ammonium salt-73 0.0001~1wt% Salicylic acid 20~40wt% Taurine 0.001~3% The rest was deionized water.

4. The salicylic acid nanocomposite gel according to claim 3, characterized in that: The mass percentage of salicylic acid is 20-35%; the mass percentage of quaternary ammonium salt-73 is 0.0001-0.5wt%; the mass percentage of taurine is 0.01-3%; more preferably, the mass percentage of salicylic acid is 30%; the mass percentage of quaternary ammonium salt-73 is 0.5wt%; and the mass percentage of taurine is 3%.

5. The salicylic acid nanocomposite gel according to claim 3, characterized in that: The mass percentage of the polyol is 15% to 30wt%; the polyol is selected from one or more of glycerol, sorbitol, polyethylene glycol-400, 1,2-butylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, 1,2-hexanediol, 1,2-pentanediol, and octyl dodecanol. The mass percentage of the lipid is 5% to 20wt%; the lipid is selected from one or more of vegetable oil, isopropyl palmitate, isopropyl myristate, caprylic / capric triglyceride, polyethylene glycol lauric acid glyceride, caprylic / capric acid polyethylene glycol glyceride, polyethylene glycol stearic acid glyceride, glyceryl stearate, linoleic acid glyceride, caprylic / capric cocoa butter, propylene glycol monocaprylate, propylene glycol dicaprylate, acetylated monoglyceride, cetyl alcohol, stearyl alcohol and cetearyl alcohol. The mass percentage of the emulsifier is 5% to 30wt%; the emulsifier is selected from one or more of PEG-15 lauryl glyceride, polysorbate-20, polysorbate-60, polysorbate-80, PEG-12 stearate, PEG-24 cholesterol ether, PEG-40 hydrogenated castor oil, sucrose stearate, and PEG-20 methyl glucose sesquistearate. The mass percentage of the auxiliary emulsifier is 15% to 40wt%; the auxiliary emulsifier is selected from one or more of PPG-26-butanol polyether-26, diethoxydiglycol, tridecyl alcohol polyether-9, coconut oil alcohol polyether-7, PPG-1-PEG-9 lauryl glycol ether, and / or, The antioxidant is selected from one or more of tocopherol acetate, sodium gluconate, tocopherol (vitamin E), and tert-butyl paramethoxyphenol.

6. The method for preparing salicylic acid nanocomposite gel according to any one of claims 1 to 5, characterized in that: The steps include: 1) mixing lipid, salicylic acid, quaternary ammonium salt-73, antioxidant, emulsifier and co-emulsifier to obtain an oil phase; 2) mixing polyol, taurine and deionized water to obtain an aqueous phase; 3) adding the water phase to the oil phase, and after mixing, performing micronization treatment after mixing to obtain a micron-sized dispersion; 4) subjecting the micron-sized dispersion to nano-treatment to obtain the salicylic acid nanocomposite gel.

7. The preparation method according to claim 6, characterized in that: In step 1), the mixing temperature is preferably 25 to 75° C., more preferably 50 to 65° C. The mixing of the present invention is preferably carried out in a water bath until the components are evenly dispersed, and / or, In step 2), the mixing temperature is preferably 25 to 75° C., more preferably 50 to 65° C. The mixing of the present invention is preferably carried out in a water bath until the components are evenly dispersed, and / or, In step 3), the aqueous phase is added to the oil phase under stirring; the stirring speed is preferably 200-600 rpm; the micronization treatment is achieved by high-speed shear emulsification; the speed of the high-speed shear emulsification is 2000-10000 rpm, preferably 5000-10000 rpm, the time is 3-15 min, preferably 3-6 min, and / or, In step 4), the method of achieving the nano-treatment includes high-pressure homogenization treatment or high-speed microfluidization treatment; the pressure of the high-pressure homogenization treatment is 400-1500 bar, preferably 300-1600 bar; the number of treatments is 2-10 times, preferably 2-6 times; the pressure of the high-pressure microfluidization treatment is 200-2000 bar, preferably 300-2000 bar, and the number of treatments is 2-10 times, preferably 2-6 times.

8. The preparation method according to claim 6 or 7, characterized in that: The prepared salicylic acid nano composite gel particles have a particle size between 10 and 100 nm and are nano composites.

9. Use of the salicylic acid nanocomposite gel according to any one of claims 1 to 5, or the salicylic acid nanocomposite gel prepared by the preparation method according to any one of claims 6 to 8 in the preparation of cosmetics.

10. The use according to claim 9, characterized in that: It includes applications in improving and treating acne, and its use method is compounding or direct application.

Citation Information

Cited By

  • Tea polyphenol composition with good stability and good in-vivo oxidation resistance and preparation method thereof

    CN122461195A

  • A tea polyphenol composition with good stability and in-vivo antioxidant property and a preparation method thereof

    CN122461195B

  • A mild alkaline buffered cornu-cutting cleansing composition and method of making and using same

    CN122894242A